Strategi Rantai Pasok Sayuran Organik Berbasis Petani di Kecamatan Pangalengan, Kabupaten Bandung - Siti Kipdiyah; Musa Hubeis; Budi Suharjo (Institut Pertanian Bogor, 2013)
Healthy lifesyle with the slogan “Back to Nature” has become a new trend of the society. Directorate of Processing and Marketing, Ministry of Agriculture in Indonesia has initiated the program